2013
DOI: 10.1007/s10916-013-9930-y
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Patients Between Five Urban Teaching Hospitals in Chicago

Abstract: To quantify the extent of patient sharing and inpatient care fragmentation among patients discharged from a cohort of Chicago hospitals. Admission and discharge dates and patient ZIP codes from 5 hospitals over 2 years were matched with an encryption algorithm. Admission to more than one hospital was considered fragmented care. The association between fragmentation and socio-economic variables using ZIP-code data from the 2000 US Census was measured. Using validation from one hospital, patient matching using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Fourth, the generalizability of our findings may be limited given the unique geographic location of these hospitals: Manhattan is the most densely populated county in the United States. However, crossover is common in studies of other locations, including 23–31% of acute care patients in Massachusetts and Indiana, and at least 6% of inpatient admissions in five Chicago hospitals …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the generalizability of our findings may be limited given the unique geographic location of these hospitals: Manhattan is the most densely populated county in the United States. However, crossover is common in studies of other locations, including 23–31% of acute care patients in Massachusetts and Indiana, and at least 6% of inpatient admissions in five Chicago hospitals …”
Section: Discussionmentioning
confidence: 99%
“…Crossover is common: statewide studies in Massachusetts and Indiana have found that 23–31% of acute care patients visit more than one acute care setting over 3–5 years . A study of five Chicago hospitals found 6% of inpatient admissions were of patients who were admitted to multiple hospitals over 2 years …”
mentioning
confidence: 99%
“…11 These systems comprise approximately 42% of the total inpatient beds in Chicago. Analysts at each institution extracted data from their data warehouse based on a specified data model.…”
Section: Methodsmentioning
confidence: 99%
“…To better understand the strengths and weaknesses of electronic data research networks and traditional cohorts for the ascertainment of demographics, CVD risk factors, and CVD events, we directly compared individual-level data from HealthLNK 11 —a research database of approximately 2.95 million Chicago area residents with extracted electronic data merged from six, large health systems—to data from the Multi-Ethnic Study of Atherosclerosis (MESA), a community-based, cardiovascular disease (CVD) cohort. We hypothesized there would be a large amount of discordance for demographics, blood pressure (BP), body mass index (BMI), CVD risk factors, and CVD events between HealthLNK and MESA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all institutions have policies, procedures, and practices designed to safeguard the use of clinical information for research purposes. As the CAPriCORN CDRN evolves, we will expand development of software and processes to support production of secure hash-based deidentified clinical datasets to allow patient disambiguation across disparate healthcare sites,7 while ensuring data security for patient data in CAPriCORN.…”
Section: Security and Privacymentioning
confidence: 99%